KRITERIA PERJANJIAN INTERNASIONAL YANG HARUS MENDAPATKAN PERSETUJUAN DEWAN PERWAKILAN RAKYAT - Setyo Widagdo; Ikaningtyas Ikaningtyas (Trunojoyo Madura University, 2022)
This article discusses the criteria for international agreements that must get approval from Indonesian Legislative Assembly with focus on two problem what is the legal implications of Constitutional Court decision number 33/PUU-XVI/2018 for the criteria of international agreements that must be approved by Indonesian Legislative Assembly and how to determine the criteria of the international treaties that have broad and fundamental effects on people's lives which is related to the country’s financial burden. This is a normative legal research. The results of this study is that the legal implications of the Constitutional Court's decision for the criteria of international agreements which must have approval of Indonesian Legislative Assembly should be positive. Asides from not giving any limit of the criteria, it can also be used as a control for the government carelessness in ratifying international agreements in trading which is almost always using Presidential Regulation instrument. To determine the criteria that an international agreement has broad consequences and fundamentals related to the country’s financial burden or require establishment of regulation, is carried out through a consultation mechanism, and the results of this consultation are recommendations and respected.